STRATEGI PENGELOLAAN LAHAN GAMBUT PROVINSI RIAU BERBASIS EKONOMI SIRKULAR - Zamaya, Yelly (Jurnal Pendidikan Ekonomi, 2024)
This research was conducted with the aim of finding a strategy for peatland management in Riau Province based on circular economy. Circular economy focuses on efficient use of resources, waste reduction, and recycling as a solution to achieve economic growth that is more balanced with environmental sustainability. This research uses qualitative descriptive analysis with SWOT analysis techniques. From the SWOT analysis, various strategies were formulated that can be used for peatland management in Riau Province. Strategies that are highly feasible for circular economy-based peatland management in Riau Province by looking at existing strengths and opportunities. These management strategies are utilising sustainable and innovative approaches to respond to the demand for environmentally friendly products; using technology and knowledge to strengthen supportive government policies; and increasing cooperation with funding and investment institutions.